2015
DOI: 10.1002/ddr.21248
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Inhalation of the M3 Receptor Antagonist Bencycloquidium Bromide in A Mouse Cigarette Smoke‐Induced Airway Inflammation Model

Abstract: Bencycloquidium bromide (BCQB), a novel M3 receptor antagonist, alleviates airway hyperresponsiveness, inflammation, and airway remodeling in a murine model of asthma. The aim of this study was to investigate the anti-inflammatory activity of inhaled BCQB in a cigarette smoke (CS)-induced model of acute lung inflammation. Mice exposed to CS developed chronic obstructive pulmonary disease (COPD). Inhalation of BCQB suppressed the accumulation of neutrophils and macrophages in airways and lung and also inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Of the 268 potentially relevant records identified in the initial search, 43 studies were deemed eligible for a qualitative analysis. Overall, this systematic review included data obtained from 28 in vivo studies performed on research animals [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], 11 in vitro studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], 3 studies conducted both in vitro and in vivo [ 69 , 70 , 71 ], and 1 clinical study performed in patients with COPD and then conducted ex vivo [ 72 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 268 potentially relevant records identified in the initial search, 43 studies were deemed eligible for a qualitative analysis. Overall, this systematic review included data obtained from 28 in vivo studies performed on research animals [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], 11 in vitro studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], 3 studies conducted both in vitro and in vivo [ 69 , 70 , 71 ], and 1 clinical study performed in patients with COPD and then conducted ex vivo [ 72 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In ICR mice exposure to CS for 4 days increased the number of total inflammatory cells, neutrophils, macrophages, and lymphocytes, and produced the gene and protein overexpression of IL-1β, KC, and TNF-α, MCP-1, and TGF-β1 in the BALf and lung tissues [ 32 , 35 ]. CS also increased the level of MMP-9 and reduced TIMP-1 in lung homogenate [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…26 In the ChiCTR2000030924 study, BCQB nasal spray four times daily per nostril proved effective and safe in the treatment of rhinorrhoea as well as sneezing, nasal congestion and itching for patients with persistent allergic rhinitis. 27 Although an inhaled form for patients with COPD was tested in 2015 in a cigarette-exposed murine model, 28 no further studies for a lung formulation have been published.…”
Section: Bencycloquidiummentioning
confidence: 99%
“…In 1995, Chang found that M-AChR density was regionally increased in asthmatic guinea pigs, and M-AChR grains in the bronchial/ bronchiolar smooth muscle and bronchial mucosal epithelium were significantly more numerous than in those of the control group (Chang, 1995). Kistemaker demonstrated that acetylcholine regulates inflammation via M 3 receptors on structural cells (Kistemaker et al, 2015), and Zhang suggested that bencycloquidium bromide (BCQB; a novel M 3 receptor antagonist) might be used in a potential therapy for inflammation in cigarette smoke-induced pulmonary diseases (Zhang et al, 2015). Other authors found that M 2 -AChR functions were reduced in asthmatic guinea pigs, mice, rats, and human patients.…”
Section: Introductionmentioning
confidence: 99%